Dampak Covid 19 Terhadap Pembelajaran Daring Di Perguruan Tinggi (FKIP, Universitas Palangka Raya, 2020)
The purpose of this study was to identify the constraints and impacts of online teaching and learning at home as a result of the COVID-19 pandemic. This research uses an exploratory case study method and the research approach uses a qualitative case study method which is used to obtain information on the impact of the COVID-19 pandemic on teaching and learning activities in higher education. In this study, participants were 8 students and lecturers at the Pattimura University Economic Education Study Program. For confidentiality purposes, participants are given the initials P1, P2, P3, P4, P5, P6, P7 and P8. Semi-structured interviews were conducted and a list of questions compiled for interviews was developed based on related literature. The results of this study are that there are several obstacles and impacts experienced by students and lecturers in online teaching and learning activities, namely the constraints for students are the lack of facilities and infrastructure and unstable signals, while the impact for students is the increase in the cost of purchasing internet quota, lack of understanding of course materials. and too many tasks. Constraints for lecturers are signals that are not stable, human resources are not ready and the lack of infrastructure owned by students, the impact on RPS lecturers and unsuitable syllabi, non-objective scoring and decreasing quality of learning.